Distress in European Banks : An Analysis Basedon a New Dataset - Poghosyan, Tigran; Cihak, Martin (Washington, D.C. : International Monetary Fund, 2009)
The global financial crisis has highlighted the importance of early identification of weak banks: when problems are identified late, solutions are much more costly. Until recently, Europe has seen only a small number of outright bank failures, which made the estimation of early warning models for bank supervision very difficult. This paper presents a unique database of individual bank distress across the European Union from mid-1990s to 2008. Using this data set, we analyze the causes of banking distress in Europe. We identify a set of indicators and thresholds that can help to distinguish sound banks from those vulnerable to financial distress.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet